Rapid wide-field heterodyne interferometry with custom 2D CMOS camera - Zhang, J.; See, C.W.; Smith, R.J.; Johnston, N.S.; Pitter, M.C.; Somekh, M.G.; Light, R.A. (Institution of Engineering and Technology, 2015)
A wide-field pseudo-heterodyne interference contrast microscope is described, which employs a complementary metal–oxide semiconductor (CMOS) phase-sensitive camera. The use of multiple wells in the camera enables extremely rapid measurement of a full phase field at high resolution and the modulation frequency is not limited by the camera frame rate. The high data acquisition frequency allows the effects of microphonics to be frozen to mitigate the effect of low-frequency disturbance.